Delineation of Waterlogging Areas of Muktsar District, Punjab using Remote Sensing Technique - Singh, J.P.; Singh, Harcharan; Shakya, S.K.; Mathur, Ajay (Journal of Soil and Water Conservation, 2022)
There are several low-lying areas in the country that are affected by waterlogging due to absence of gravity outlet The seepage from above canal network, accumulation of runoff water from upland to low-lying areas and cropping pattern are the chief cause of waterlogging. The extent of waterlogging and its effect on existing crop on each day of the monsoon or post monsoon season could be delineated using Remote Sensing Technique. The waterlogging in Muktsar district of southwest Punjab was very severe in the year 1995 and 1997. During 1997, more than one latch ha. area of this region was experiencing flood like situation and crop worth Rs. 200 crore was damaged. The waterlogged area of Muktsar district of southwest Punjab was delineated for the year 1995 and 1997 using FCC and Classified Imagery. The FCC of IRS-1B LISS-H for 1995 and IRS-1C LISS:111 for 1997 and Classified map on September 18, 1995 and September 19, 1997 were prepared with satellite data. The total waterlogged area was demarcated and estimated to be 5188.819 ha. on September 18, 1995 and 22917.84 ha. on September 19, 1997 using remote sensing data and technique. The increase in waterlogging has been observed to be four times over a period of two years i.e. from 1995 to 1997.